1991
DOI: 10.1099/00207713-41-4-479
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Streptomyces spp. Causing Potato Scab

Abstract: The levels of DNA-DNA hybridization among members of the three major groups of Streptomyces spp. that cause potato scab did not exceed 20% for any pair. The majority of the Streptomyces scabies strains which we examined exhibited greater than 70% relatedness to the type strain, although values as low as 21% were obtained. The levels of homology between S . scabies and nonpathogenic type strains belonging to the Diastatochromogenes group ranged from 10 to 42 9% , while the reciprocal values obtained with labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 19 publications
6
52
0
Order By: Relevance
“…We obtained GjC content of 70n3 mol % for the reference strains, S. scabies CFBP 4517 T and S. acidiscabies CFBP 4539 T , which was consistent with the values of 70n5 mol % (CFBP 4517 T ) and 71n1 mol % (CFBP 4539 T ) determined previously (Healy & Lambert, 1991).…”
Section: Dna Base Compositionsupporting
confidence: 75%
See 1 more Smart Citation
“…We obtained GjC content of 70n3 mol % for the reference strains, S. scabies CFBP 4517 T and S. acidiscabies CFBP 4539 T , which was consistent with the values of 70n5 mol % (CFBP 4517 T ) and 71n1 mol % (CFBP 4539 T ) determined previously (Healy & Lambert, 1991).…”
Section: Dna Base Compositionsupporting
confidence: 75%
“…S. scabies strains form a relatively homogeneous group on the basis of the limited number of phenotypic features studied (Lambert & Loria, 1989a ;Faucher et al, 1992). However, molecular studies involving techniques such as DNA-DNA hybridization have shown a great diversity within the strains identified as S. scabies (Healy & Lambert, 1991 ;Paradis et al, 1994). Other species, including Streptomyces acidiscabies (Bonde & McIntyre, 1968 ;Lambert & Loria, 1989b), Streptomyces caviscabies (Faucher et al, 1995 ;Goyer et al, 1996), and other as yet unnamed species of Streptomyces (Doering-Saad et al, 1992), also cause common scab.…”
mentioning
confidence: 99%
“…However, our observation is in line with a low level of DNA-DNA relatedness between the two type strains (43 %) observed in an earlier study (Healy & Lambert, 1991). Furthermore, a comparison of earlier phenotypic descriptions of the two species, such as melanin production by S. griseus in tyrosine agar in contrast to S. setonii and differences in carbon source utilization patterns between the two (Shirling & Gottlieb, 1968, clearly supports our observation.…”
Section: Taxonomic Conclusionsupporting
confidence: 79%
“…With the advent of molecular genetic characterization of CS-causing species, it became apparent that Streptomyces scabies was a complex of species (BouchekMechiche et al 2000;Bukhalid et al 2002;Doering-Saad et al 1992;Healy and Lambert 1991;Takeuchi et al 1996). Morphological, physiological and molecular evidence currently supports the designation of about ten CS-causing species known from one or more geographic locations around the world.…”
Section: Discussionmentioning
confidence: 99%